Clinical and Functional Effects of Kinesiotaping and Physiotherapy in Grade 2 or Less Osteoarthritis Following Degenerative Meniscal Tears in Football Players – A Randomized Control Trial - Alrawaili, SaudM. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2025)
Degenerative meniscal tears are a common cause of knee pain commonly diagnosed in football players and considered to be a major risk factor for development of knee osteoarthritis (OA). This study aimed to investigate the clinical and functional effects of a combined intervention involving kinesiotaping and physiotherapy in football players diagnosed with Grade 2 or less Osteoarthritis following degenerative meniscal tears.Fifty-six football players following meniscus injury with grade 2 or less OA were randomly assigned into two groups (Kinesiotaping and physiotherapy – Group A and Physiotherapy alone – Group B). Both groups received a same physiotherapy program while group A received the kinesiotaping after receiving physiotherapy. Pain intensity, functional disability, sports performance and quality of life were measured with visual analogue scale (VAS), WOMAC scale, timed up and go test, 40m zig-zag test and short form-12questionnaire. The basic demographic and clinical characters were measured. The mean (95% CI) and standard deviation between groups was estimated using multi model repeated measure (MMRM) analysis. The results of the mixed model repeated measure analysis of variance showed significant interaction between groups (A and B) and time (before and after intervention) (p=0.001). After eight weeks of intervention, and at the end of 6 months of follow-up, the pain intensity is 3.1 (95% CI 2.94 to 3.25), functional disability (WOMAC) 30.0 (95% CI 28.16 to –31.83), TUG 4.9 (95% CI 4.34 to 5.45), 40m zig zag test 6.3 (95% CI 5.54 to 7.05) and quality of life –30.4 (95% CI –33.2 to –27.5) shows more improvement (p=0.001) in group A than group B. The results showed that kinesiotaping with physiotherapy showed significant improvement in pain intensity, functional status, sports performance and quality of life in patients with grade 2 or less osteoarthritisfollowing degenerative meniscal tears in football players.
Keywords: meniscus tear; grade 2 osteoarthritis; Kinesiotaping; Patellar taping; functional status